The dorsal attentional system in oculomotor learning of predictive information - Tseng, Philip; Chang, Chi-Fu; Chiau, Hui-Yan; Liang, Wei-Kuang; Liu, Chia-Lun; Hsu, Tzu-Yu; Hung, Daisy L.; Tzeng, Ovid J.; Juan, Chi-Hung (Frontiers in Human Neuroscience, 2013)
The dorsal attentional network is known for its role in directing top-down visual attention toward task-relevant stimuli. This goal-directed nature of the dorsal network makes it a suitable candidate for processing and extracting predictive information from the visual environment. In this review we briefly summarize some of the findings that delineate the neural substrates that contribute to predictive learning at both levels within the dorsal attentional system: including the frontal eye field (FEF) and posterior parietal cortex (PPC). We also discuss the similarities and differences between these two regions when it comes to learning predictive information. The current findings from the literature suggest that the FEFs may be more involved in top-down spatial attention, whereas the parietal cortex is involved in processing task-relevant attentional influences driven by stimulus salience, both contribute to the processing of predictive cues at different time points.